Scoping review protocol to investigate the experience of intimate partner violence among Black women and children living in the United Kingdom and how domestic violence specialist organisations support them to thrive - Cynthia Dawes; Claire Powell; Carol Rivas (PLoS ONE, 2026)
Background This protocol focuses on male-perpetrated intimate partner violence and aims to explore how Black women and children are supported to thrive post-intimate partner violence. Although this form of violence affects women across all cultures, Black women remain significantly underrepresented in the existing literature and often face various barriers to disclosure and help-seeking, including patriarchal silencing, immigration status, language issues and unsupportive attitudes of staff. It remains unclear how they transition from surviving to thriving individuals. The scoping review addresses the question: What are the lived experiences of intimate partner violence among Black women and children, and what factors shape their concept of thrivership?. The scoping review explores the knowledge gap in understanding how Black women and children affected by systemic oppression at the intersection of race, immigration and gender, experience thriving after leaving their abusive relationship. It examines existing research to identify key factors that contribute to their thrivership in the UK context. This study protocol provides a detailed outline of the planned methodology for conducting the scoping review. Methods and analysis The scoping review of qualitative evidence will be guided by the five steps of the framework proposed by Arksey and Malley, which include identifying the research question, identifying relevant studies, selecting studies, charting the data, collating, summarising and reporting the results and an additional consultation stage with stakeholders. The results from the scoping review will be presented using the PRISMA Extension for Scoping Reviews (PRISMA-ScR), and the data will be analysed using thematic analysis. The databases searched will be Ovid PsycINFO, Scopus, ASSIA and Web of Science. Ethics and dissemination The anticipated results from the review will help generate new ideas for future studies and inform policy. The findings will be submitted for publication in relevant peer-reviewed journals and presented at conferences and to appropriate stakeholders. No ethics is required as this is a review without human participants being involved. This protocol has been registered on the Open Science Framework (OSF).